Application of DBN deep learning algorithm in anti stealing electricity system - Dandan LI; Bingyu GE; Wenwen HUANG; Lei XIE; Shengqi QIAN (Dianxin kexue, 2019)
With the development of economy,the electric power demand increases gradually,but because of the relative backwardness in the automation of electricity,the phenomenon of electric stealing is common.But the traditional anti electric stealing means generally centered around how to strengthen the technical transformation of the electric energy metering device,and the management efficiency is low.The purpose of deep learning is to use the method of constructing the multi-layer neural network model.To learn the potential features of image,text,voice and other data,it also has good effect on the classification problem.The successful application of the deep learning algorithm in many complex fields provides a new effective way to solve the problem of anti stealing electricity.The structure and learning algorithm of DBN and the anti-stealing model based on DBN algorithm was mainly introduced.Finally,experiments were carried out and the results were analyzed.